Development of Interactive Teaching Materials in Indonesian for Grade VI Elementary School Students - Widodo, Joko (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Interactive teaching materials are written materials in the form of sheets of paper that are bound and given covers and that present knowledge that is arranged systematically. This research aims to develop valid, effective, and practical teaching materials. This study uses a 4D research model with four stages: defining, designing, developing, and deploying. This teaching material has been validated by several experts, namely material experts, media design experts, and linguists. This study had three trials: individual trials, small group trials, and large group trials. Based on the combined percentage of validity of interactive teaching materials, according to experts, a percentage of 89% is categorized as "very valid." The practicality of interactive teaching materials is measured through RPP implementation sheets conducted in large group trials of meeting 1 of 92.72% and large group trials of meeting 2 of 92.98% categorized as "very practical." Effectiveness was obtained from large group trials with a percentage of 92.33% categorized as "very effective." Based on these results, it can be concluded that interactive teaching materials in grade VI SD Muhammadiyah 8 Dau Malang are suitable for use.